2021
DOI: 10.3855/jidc.14709
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of severe COVID-19 pneumonia managed with supportive care in Palestine: an experience from a developing country

Abstract: Introduction: About 14% of COVID-19 patients experience severe symptoms and require hospitalization. Managing these patients could be challenging for limited-resource countries, such as Palestine. This study aimed to evaluate hospitalized severe COVID-19 patients' treatment outcomes managed with supportive care and steroids. Methodology: This was a single-center observational retrospective cohort study that enrolled COVID-19 patients admitted to the “Martyrs medical military complex- COVID Hospital” in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…After screening by abstract and title, 571 articles were selected for full-text assessment. In total, 157 studies evaluating 948,309 patients were included in the meta-analysis (9–159). The characteristics of all the included studies are shown in Table S1 (http://links.lww.com/CCX/B152).…”
Section: Resultsmentioning
confidence: 99%
“…After screening by abstract and title, 571 articles were selected for full-text assessment. In total, 157 studies evaluating 948,309 patients were included in the meta-analysis (9–159). The characteristics of all the included studies are shown in Table S1 (http://links.lww.com/CCX/B152).…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al found that the oxygen saturation level had a good predictive performance for predicting death. 18 Despite the lack of published statistics on NEWS2's effectiveness in controlling COVID-19 patients' clinical deterioration, this study showed that NEWS2 was good at predicting deteriorating patients based on their oxygen requirement, with an acceptable level of sensitivity and specificity for LFO, high-flow oxygen (HFO), and mechanical ventilation (intermittent mandatory ventilation [IMV]).…”
Section: Discussionmentioning
confidence: 75%
“…The results of the INCREASE study led to the FDA approval of inhaled treprostinil for PH-ILD in April 2021. This step made it the first FDA-approved medication specifically for PH-ILD[ 46 ].…”
Section: Ph-directed Therapies: Beyond the Underlying Ildmentioning
confidence: 99%
“…Practically, inhaled treprostinil is administered four times daily and is titrated to a maximum tolerated dose up to 72 mcg or 12 breaths per dose [ 46 ]. Flushing, headache, diarrhea, and cough are the most common dose-limiting symptoms.…”
Section: Ph-directed Therapies: Beyond the Underlying Ildmentioning
confidence: 99%
See 1 more Smart Citation